Analysis of differentially expressed genes after ex vivo X-rays irradiation of human peripheral white blood cells - Biolatti, Vanesa; Negrin, Lara Maria; Bellora, Nicolás; Ibañez, Irene Laura (Fundación Revista Medicina, 2018)
Fil: Biolatti, Vanesa. Comisión Nacional de Energía Atómica; Argentina